Human Papillomavirus (HPV) Vaccine Uptake and the Willingness to Receive the HPV Vaccination among Female College Students in China: A Multicenter Study - You, Dingyun; Han, Liyuan; Li, Lian; Hu, Jingcen; Zimet, Gregory D.; Alias, Haridah; Danaee, Mahmoud; Cai, Le; Zeng, Fangfang; Wong, Li Ping (MDPI, 2020)
Background: This study aimed to determine human papillomavirus (HPV) vaccine uptake and willingness to receive HPV vaccination among female college students, in China, and its associated factors. Methods: An online cross‐sectional survey of female college students across the eastern, central, and western regions of China was undertaken between April and September 2019. Partial least squares structural equation modeling (PLS‐SEM) was used to examine factors associated with the HPV vaccine uptake and willingness to receive the HPV vaccine. Results: Among the total 4220 students who participated in this study, 11.0% reported having been vaccinated against HPV. There are direct effects of indicators of higher socioeconomic status, older age (β = 0.084 and p = 0.006), and geographical region (residing in Eastern China, β = 0.033, and p = 0.024) on HPV vaccine uptake. Higher knowledge (β = 0.062 and p < 0.000) and perceived susceptibility (β = 0.043 and p = 0.002) were also predictors of HPV vaccine uptake. Of those who had not received the HPV vaccine, 53.5% expressed a willingness to do so. Likewise, social economic status indicators were associated with the willingness to receive the HPV vaccine. Total knowledge score (β = 0.138 and p < 0.001), both perceived susceptibility (β = 0.092 and p < 0.001) and perceived benefit (β = 0.088 and p < 0.001), and sexual experience (β = 0.041 and p = 0.007) had a positive and significant direct effect on the willingness to receive the HPV vaccine, while perceived barriers (β = −0.071 and p < 0.001) had a negative effect on the willingness to receive the HPV vaccine. Conclusions: Geographical region and socioeconomic disparities in the HPV vaccination uptake rate and willingness to receive the HPV vaccine provide valuable information for public health planning that aims to improve vaccination rates in underserved areas in China. The influence of knowledge and perceptions of HPV vaccination suggests the importance of communication for HPV immunization. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.